1984
DOI: 10.1227/00006123-198401000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Neoplasms during the First Year of Life: Analysis of One Hundred Consecutive Cases

Abstract: One hundred infants with intracranial tumors symptomatic during the 1st year of life were studied. They differed from older children in having a higher percentage of supratentorial tumors and in the fact that 90% of the tumors were of neuroectodermal origin. Vomiting, alteration of psychomotor development, and macrocrania were the most common presenting features. The "diencephalic syndrome" was seen in 5 infants, and subarachnoid hemorrhage due to tumor was diagnosed in 4. Computed tomography as the primary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
60
6
8

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 0 publications
15
60
6
8
Order By: Relevance
“…As described by others [1, 3, 4, 7, 10, 13, 14, 15, 26, 32, 34, 35, 36], we also found a significantly higher incidence of supratentorial tumors in the group aged 1–12 months, with an inverse tendency in the second and third year of age. Furthermore, the majority (26/36) of the tumors originated from midline structures: fourth ventricle and cerebellar vermis and the suprasellar-chiasmatic-hypothalamic region were the commoner locations, respectively, below and above the tentorium.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As described by others [1, 3, 4, 7, 10, 13, 14, 15, 26, 32, 34, 35, 36], we also found a significantly higher incidence of supratentorial tumors in the group aged 1–12 months, with an inverse tendency in the second and third year of age. Furthermore, the majority (26/36) of the tumors originated from midline structures: fourth ventricle and cerebellar vermis and the suprasellar-chiasmatic-hypothalamic region were the commoner locations, respectively, below and above the tentorium.…”
Section: Discussionsupporting
confidence: 91%
“…In our series, surgical mortality was 10.2%; in other series [10, 12, 13, 15, 25, 32, 34, 35, 36, 38]it ranged from 33% to less than 5% in more recent years. On the question of morbidity, we noted new or worse neurological deficit in the postoperative period in 30% of the cases, but only 12% of these lasted more than 6 months; these incidences are similar to those described by others [8, 13].…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The high incidence of total resection in the present series is due to the high proportion of choroid plexus tumors, where the tumors have a good plane and resection is possible after the vascular pedicle is visualized. Operative and perioperative mortality varied, ranging from no mortality as reported by Haddad et al [9] to 33% as reported by Jooma et al [10]. Tewari et al [11] reported a mortality of 57%, though this series included only supratentorial tumors.…”
Section: Discussionmentioning
confidence: 86%
“…9,12,13,16,23 Their benign nature and intraventricular, noninfiltrative nature renders them surgically curable. 15,20,27 Gross-total resection has been associated with excellent prognosis, 9,18,20 with 5-year survival being close to 100% after complete resection, but survival is only 56% after subtotal resection.…”
Section: Discussionmentioning
confidence: 99%